Current Physical Conditioning Knowledge of High-School Athletic Coaches in the Johannesburg-North Education District – A Cross Sectional Survey - Marais, Anna M. (University of Pretoria, 2013)
Dissertation (MPhysT)--University of Pretoria, 2013.